Jogo sério como ferramenta para o auxílio da educação ambiental nos anos iniciais do ensino fundamental - Kirchhof, Edson Francisco Borim (2023)
Since the beginning of human social organization, man has been modifying the planet in different ways, generating technological progress and, as a consequence, environmental problems may arise. Environmental education is important for society as a way of teaching new generations to live in harmony with nature, building social, moral and ethical values. Serious games are those that recreate situations and problems from reality for educational purposes. The present work presents the development process of a serious game to help environmental education in the early years of elementary school. The proposal contemplates the mobility and flexibility of current learning, as well as the need for playful and challenging materials for children with a focus on environmental education, becoming a motivating pedagogical strategy in the construction of knowledge in the early years of elementary school. For the development of the game, the Constructo 3 game engine was used. The game's genre is a farm simulator focused on sustainability with free choices. The game evaluation was carried out with 74 participants, using a series of questionnaires defined in the MEEGA+ methodology, with questions regarding usability and player experience. The evaluation of the game shows positive results and approval to be used as an auxiliary tool in the teaching of environmental education.